2020
DOI: 10.1021/acs.joc.0c00154
|View full text |Cite
|
Sign up to set email alerts
|

Access to Hetero-Benzyl Scaffolds via Transient-Ligand-Enabled Direct γ-C(sp3)–H Arylation of 3-Methylheteroarene-2-Carbaldehydes

Abstract: An efficient and straightforward method has been developed for the synthesis of β-benzyl-substituted 5-membered heterocyclic carbaldehydes via transient directing-group-enabled direct γ-C(sp 3 )−H arylation of 3-methylheteroarene-2-carbaldehydes. A wide range of 3-methylheteroarene carbaldehydes undergo coupling with a variety of aryl iodides, including less reactive iodo pyridine derivatives to provide a library of highly selective functionalized products in good to excellent yields. Some of these products ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…l -Valine was found to be an effective transient DG in the γ-arylation of 3-methylheteroarene-2-carbaldehydes (Scheme ). Initial optimization found that a 9:1 HFIP/AcOH medium delivered product in 94% yield, whereas HFIP or AcOH alone led to yields of 37% and 75%, respectively. Substrates such as thiophenes, benzothiophenes, and benzofurans were readily functionalized in yields up to 98%; however, indoles were not amenable to this method.…”
Section: C–h Functionalization Reactionsmentioning
confidence: 99%
“…l -Valine was found to be an effective transient DG in the γ-arylation of 3-methylheteroarene-2-carbaldehydes (Scheme ). Initial optimization found that a 9:1 HFIP/AcOH medium delivered product in 94% yield, whereas HFIP or AcOH alone led to yields of 37% and 75%, respectively. Substrates such as thiophenes, benzothiophenes, and benzofurans were readily functionalized in yields up to 98%; however, indoles were not amenable to this method.…”
Section: C–h Functionalization Reactionsmentioning
confidence: 99%
“…Indeed, while the groups of Li, and Liu and Lou could demonstrate the ability of semicarbazide [101] and 2-dimethylaminoethylamine, [102] respectively, to act as efficient transient directing mediators (Scheme 60, c and d), the group of Bao extended the use of acetyl hydrazine as a transient directing mediator to aluminasupported nanoparticles of palladium(0) (Scheme 60, e). [103] Eventually, the groups of Bhat, Li and Zhang could extend the method to the arylation of 3-methylheteroarene-2-carbaldehydes with L-valine (Scheme 60, f), [104] to the use of glycinamide hydrochloride as a transient directing mediator (Scheme 60, g) [105] and to the biarylation of ortho-methylbenzaldehydes with cyclic diaryliodonium salt reactants using L-tert-leucine (Scheme 60, h), [106] respectively.…”
Section: (Hetero)arylation Reactions 42111 Benzylic C(sp 3 )à H Bondmentioning
confidence: 99%
“…The activation of benzylic C(sp 3 )-H has seen some key advances in the past two years, with both new directing groups and novel coupling partners being reported. [43][44][45][46][47][48][49][50] The benzylic C-H bonds are electronically activated by the presence of the aryl group, and are relatively constrained geometrically. Yi and Zhang reported a method to construct polyaromatic hydrocarbons from o-tolualdehydes and di/tri-iodoarenes (Scheme 13a).…”
Section: Benzylic C(sp 3 )-H Functionalisation Of Benzaldehydesmentioning
confidence: 99%
“…The arylation of 3-methyl(benzo)thiophene carboxaldehydes and3-methylbenzofuran carboxaldehydes were demonstrated by Bhat, using valine as an effective transient directing group for this type of benzylic substrate bearing a pentaatomic aromatic backbone (Scheme 13e). 48 A broad range of aromatics could be installed in high yields, up to 98% using 4-CO 2 Me iodobenzene as a coupling partner. Several substituted iodopyridines could also be successfully used to install heteroaromatics.…”
Section: Benzylic C(sp 3 )-H Functionalisation Of Benzaldehydesmentioning
confidence: 99%